Usman DP INSTITUSI KELUARGA DALAM PERSPEKTIF PENDIDIKAN ISLAM: Menuju Keluarga SAMAWA - usman dp (Darul Ulum: Jurnal Ilmiah Keagamaan, Pendidikan dan Kemasyarakatan, 2020)
Familiy institutions are the heart of society an the backbone to support a society to become a strong and solid society The familiy as the smallest in society has a major contribution the determines the quality of a nation. An advanced nation must start from an association of advanced families. Therefore, the role and position on the family is the first and foremost environment in instilling religious, moral, ethical values, and forming the personality its members. The family is a “Madrasah” where one someone is educated, raised, an introducated to various thing that make him grow and dedevelop optimallu in facing life. On the other hand, backwardness, iqnorance, and setbacks occur in nation are reflection on the familiy living in the natio’s society. The concept of universal Islamic teaching provides quidance and attention in encouraging the family as an institution that has a role and responsiblities of pao create an atmosphere rents must be able the process of forming a child’s superior personality and character. To achieve this goal, the role and atmosphere of comfort, tranguility, and family that is SAMAWA. Thus, the Samawa family institution is required to the able to create an Islamic educational armosphere for every occupant in obtaining inner and outer peace. Keyword: Family Institution, Islamic Education Perspective, Samawa.